Dietary Modification Alters the Intrarenal Immunologic Micromilieu and Susceptibility to Ischemic Acute Kidney Injury - Jeon, Junseok; Lee, Kyungho; Yang, Kyeong Eun; Lee, Jung Eun; Kwon, Ghee Young; Huh, Wooseong; Kim, Dae Joong; Kim, Yoon-Goo; Jang, Hye Ryoun (Frontiers in Immunology, 2021)
The versatility of intrarenal immunologic micromilieu through dietary modification and the subsequent effects on the susceptibility to ischemic acute kidney injury (AKI) are unclear. We investigated the effects of high-salt or high-fat diets on intrarenal immunologic micromilieu and the development of ischemic AKI using murine ischemic AKI and HK-2 cell hypoxia models. Four different diet regimens (control, high-fat, high-salt, and high-fat with high-salt) were provided to each group of 9-week male C57BL/6 mice for 1 or 6 weeks. After a bilateral ischemia-reperfusion injury (BIRI) operation, mice were sacrificed on day 2 and renal injury was assessed with intrarenal leukocyte infiltration. HK-2 cells were treated with NaCl or lipids. The high-fat diet increased body weight and total cholesterol, whereas the high-fat diet with high-salt did not. Although the high-salt or high-fat diet did not change the total leukocytes infiltration at 6 weeks, the high-fat diet and high-fat diet with high-salt increased intrarenal CD8 T cells. Plasma cells increased in the high-fat and high-salt diet groups. The expression of proinflammatory cytokines including TNF-α, IFN-γ, MCP-1, and RANTES was increased by the high-salt or high-fat diet, and intrarenal VEGF decreased in the high-salt and high-fat with high-salt diet groups at 6 weeks. Deterioration of renal function following BIRI tended to be aggravated by the high-fat or high-salt diet. High NaCl concentration suppressed proliferation and enhanced the expression of TLR-2 in hypoxic HK-2 cells. The high-salt or high-fat diets may enhance susceptibility to ischemic AKI by inducing proinflammatory changes to the intrarenal immunologic micromilieu.